2017
DOI: 10.4067/s0718-95162017005000037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar application on nitrogen leaching, ammonia volatilization and nitrogen use efficiency in two distinct soils

Abstract: This study was conducted to determine the effect of biochar application on nitrogen (N) leaching, ammonia (NH3) volatilization, and fertilizer N use efficiency (NUE) in two soils with different properties (loamy and sandy). Ryegrass (Lolium perenne L.) incubation experiments (with 15 N-enriched urea applied) and an N loss simulation study were conducted at biochar application rates of 2% and 4%. The results showed that 15 N utilization increased by 8.83-9.06% following the addition of biochar to sandy soil dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 26 publications
4
38
0
Order By: Relevance
“…Decreased N values in the BCH amended treatments with the B inoculum could have been related to N immobilization by BCH and this hypothesis might explain the reduced plant growth in B amended treatments of both growing cycles. Results are in accordance with the experiments on corn stover and hardwood BCH with silt loam soil and corn [39], maize stover BCH and ryegrass with loamy/sandy soil [40]. Otherwise, N content reduction in B treated plants with the reduced biomass might be explained by the B inoculum lower N 2 -fixators activity with its BCH combination comparing to the Novaferm one, with perhaps inefficient microbial population establishment of the added inoculum as suggested in studies of Dempster et al [41] where jarrah wood BCH supressed microbial development.…”
Section: Influence Of the Bch Mixed With Bacterial Inoculumssupporting
confidence: 90%
“…Decreased N values in the BCH amended treatments with the B inoculum could have been related to N immobilization by BCH and this hypothesis might explain the reduced plant growth in B amended treatments of both growing cycles. Results are in accordance with the experiments on corn stover and hardwood BCH with silt loam soil and corn [39], maize stover BCH and ryegrass with loamy/sandy soil [40]. Otherwise, N content reduction in B treated plants with the reduced biomass might be explained by the B inoculum lower N 2 -fixators activity with its BCH combination comparing to the Novaferm one, with perhaps inefficient microbial population establishment of the added inoculum as suggested in studies of Dempster et al [41] where jarrah wood BCH supressed microbial development.…”
Section: Influence Of the Bch Mixed With Bacterial Inoculumssupporting
confidence: 90%
“…The effect of high‐C‐content amendments on NO 3 –N leaching depends on complex physical, chemical, and biological processes. It has been suggested that leaching of soil NO 3 –N depends on the ability of biochar to retain NO 3 –N and NH 4 –N or on the inhibition of nitrification by clay particles (Clough, Condron, Kammann, & Müller, 2013; Liu et al., 2017). Some biochar studies have found decreased NO 3 –N leaching depending on fertilizer type, soil type, and leaching conditions, but other studies showed inconsistent effects of biochar on leaching (Fidel, Laird, & Spokas, 2018; Haider, Steffens, Moser, Müller, & Kammann, 2017; Sika & Hardie, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Low soil fertility necessitates fertilizer applications which increase cost of crop production and can result in environmental issues such as algal bloom and contamination of water bodies [1]. Biochar reportedly has good capacity to retain nutrients and improve their phyto-availability due to its numerous pores and large surface area and charge [2,3]. Recent research has shown that additions of biochar reduced nutrient losses from agricultural lands [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The nutrient regulating capacity of biochar could be attributed to its large surface area, porosity, surface charge, organic coating, and other factors, such as pH and ionic competition [2,3,21]. For example, NH 4 -N adsorption is due to cation exchange of the surface functional (e.g., phenolic and carboxylic) groups of biochar produced at relatively low (300-400 • C) temperature [22] and physical entrapment in biochars pores [23].…”
Section: Introductionmentioning
confidence: 99%